Efforts to Increase Interest and Achievement Students at Raudhatul Ulum Al Qur'an Training Park Using the Drill Method - Azis Purwanto; Suhartono; Sholeh Hasan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research mean use explore role deep drilling technique raise hasart as well as results study participant students at the Al-Qur'an Learning Park (TPA) Raudhatul Ulum, a agency Islamic religious learning in the village Margodadi, East Oku. Religion Islam has objective For form Individuals who are faithful, pious , have morals noble and responsible answer . However, in rural areas, approach innovative like use deep drilling technique upgrading Islamic religion still relatively seldom done. This research use approach qualitative with procedures ethnography use investigate and analyze How drilling method influence interest Study student as well as factors supporters and obstacles. Information collected past ask responsible, monitoring respondents , as well documentation in context activity learning at the TPA. Findings study indicated If usage drilling technique can increase participants' passion educate in a way effective to Islamic religious training at Raudhatul Ulum TPA. This method help student For strengthen reading as well as interpretation of the verses of the Koran as well increase ability they in aspects such as tajwid and tartil. Apart from that, drill also plays a role in increase performance students , okay from facet understanding Islamic religious concepts as well implementation deep Islamic values activity every day .This research share outlook means For perpetrator Islamic religious learning in rural For adopt drill method as effective alternative in increase quality learning at TPA. Implications from study This show that teachers need increase creativity and innovation in approach learning For motivating student in a way sustainable, esp in understand and apply Islamic teachings.